Motivation and L2 Receptive Vocabulary Knowledge of Spanish EFL Learners at the Official School of Languages - Canga Alonso, Andrés; Fernández Fontecha, Almudena (Miscelánea: A Journal of English and American Studies, 2014)
This study explores the relationship between the motivation and receptive vocabulary knowledge of a group of 30 EFL students in the 1st and 2nd year of the Official School of Languages intermediate level (B1) (Escuela Oficial de Idiomas - EOI). We measured their receptive vocabulary by means of the 2,000-word frequency-band from the receptive version of the VLT (2K VLT) (Schmitt, Schmitt and Clapham 2001, version 2). On the other hand, an adaptation of Gardner’s (1985) A/MTB questionnaire was used to analyse motivational levels. On a three-level scale to range learners’ motivation marks, i.e. high motivation, medium motivation, low motivation, our results evince most learners’ were highly motivated in the two years (level 3) and the rest were motivated (level 2). As could be expected in this type of language teaching, no lowly motivated learners were identified. Concerning the types of motivation, extrinsic motivation was higher than intrinsic motivation in both years. The evolution of general motivation and the two types, extrinsic and intrinsic, is not significant from the 1st to the 2nd year. Both the general motivation and the intrinsic type decrease slightly from one year to the following one. As for students’ receptive vocabulary knowledge, it increased significantly from the 1st to the 2nd year. Finally, no significant correlation was detected between this type of vocabulary and learners’ levels of general intrinsic and extrinsic motivation.